ISOKINETIC EVALUATION OF MUSCULAR STRENGTH AFTER DIFFERENT ISCHEMIC PRECONDITIONING PRESSURES: A PLACEBO-CONTROLLED RANDOMIZED CLINICAL TRIAL - da Silva Brandão, Guilherme Henrique [UNESP]; Filho, Carlos Alberto Toledo Teixeira [UNESP]; Biral, Taíse Mendes [UNESP]; de Carvalho, Flávia Alves [UNESP]; Pizzo, Eduardo [UNESP]; Vanderlei, Franciele Marques [UNESP] (Elsevier, 2024)
Background Ischemic preconditioning (IPC) is characterized as a procedure consisting of intermittent applications of cycles of non-lethal and short-duration vascular occlusion in a target limb, followed by reperfusion through inflation and deflation of a pressure cuff. Because it is a method of easy administration, usability, non-invasive, and low cost, it currently presents as an attractive ergogenic resource that has been used for performance enhancement. Despite its notoriety in the literature in recent years, there are gaps regarding the most efficient protocol to be used to obtain significant results, especially for increasing muscular strength. Objectives to compare the effect of different IPC occlusion pressures on muscular strength through maximum voluntary isometric contraction (MVIC). Methods eighty healthy men (22.10±2.86 years) were randomly divided into four groups: IPC using total occlusion pressure (TOP) [IPC-TOP], IPC with 40% more than TOP (IPC-40%), placebo (10 mmHg), and control. The IPC protocol used consisted of four cycles of ischemia and reperfusion of five minutes each, totaling 40 minutes, while the placebo underwent an intervention like IPC but with four cycles of five minutes of placebo occlusion (10mmHg) alternated with four cycles of five minutes of reperfusion (0 mmHg). In the control group, individuals remained at rest for 40 minutes. Initially, TOP evaluation was performed, followed by baseline evaluation of MVIC on an isokinetic dynamometer. Next, participants underwent the previously randomized intervention protocol. Finally, MVIC evaluation was performed again. Descriptive statistical methods and analysis of variance for repeated measures were used with a significance level of 5%. Results all analyzed groups showed a significant difference in the final evaluation compared to the baseline (p<0.05), where the levels of muscular strength decreased. Regarding the magnitude of the losses, it was observed that the IPC-40% group (Δ = -14.01Nm) presented the lowest reduction, which was statistically significant compared to the control, placebo, and IPC-TOP groups (Δ = -29.46Nm; -32.71Nm and -26.44Nm, respectively). Conclusion IPC with 40% more than the TOP was able to attenuate the reduction of muscular strength evaluated by the MVIC. Implications the present study brings important results providing an alternative technique that can be used in training and competition routines to minimize the loss of muscular strength.